Pemberdayaan Masyarakat Kabupaten Banyuasin dalam Pemanfaatan Sekam Padi Menjadi Kertas - Andi Saputra; Feliyanti Feliyanti; Riri Novita Sunarti; Ike Apriani; Ra. Hoetary Tirta Amallia; Tito Nurseha; Rr. Mini Sari Wulan; Awalul Fatiqin (Universitas Indraprasta PGRI, 2022)
Paper generally uses wood as the main raw material, which is increasingly expensive, so it requires alternative raw materials such as rice husks. Banyasin Regency is a food producer and provides high by-products (rice husks), so the researchers aim to use rice husks into paper. The method used in this study includes display data (presentation of data) the results of the utilization of rice husks, and the conclusion (conclusion) of the resulting paper. The results obtained from the use of rice husk into paper in assisting the community of the Muara Telang District, Banyasin Regency, received positive responses from the community, which was indicated by the attitude of the residents in managing the husks into paper and the paper produced had characteristics, was bright brown in color, flexible, and had a husk motif. The paper obtained from this activity is suitable to be developed as a calligraphy and other craft materials.